(untitled) (Revista Internacional de Formação de Professores, 2022)
This paper has the aim to approach, through the memory of a teacher, her professional education between 50’s and final of 70’s decade, from 20th century, when the school education lived concepts that it were reframed with the inclusion of women in the chairs of school groups. It was intended, through the application of a questionnaire, to revise the informant’s memories, taking Freitas (2003), Le Goff (2003), Santos (2006), Azevedo (2009) and Chartier (2009 e 2010), as theoretical assumptions in the construction of the study. After the analysis, looked for identify the paths covered and how difficulties faced by a woman who sought to transcend the domestic sphere, the social, economic independence and professional achievement, as teacher, mother and woman, in a time that they had few access to the culture, to the politics, women’s rights as citizen and egalitarian education. In addition, complying with the CNS 466/12, on research with human beings, to protect the identity of the informant and any form of embarrassment, it will be used a pseudonym for them.